Socialization of Operation and Maintenance of Communal PLTS to The People of Tunjungan Kutai Kartanegara Village - Rusda; Cornelius Sarri; Khairuddin Karim (Outline Journal of Community Development, 2023)
Off-grid/communal Solar Power Plant (PLTS) using photovoltaic technology is one form of renewable energy development application in Indonesia that aims to provide access to electrical energy in villages that have not been electrified in hinterland, border areas and outermost small islands, while increasing national energy independence and security. To support this goal, the Community Service Team of the Department of Electrical Engineering of Samarinda State Polytechnic carried out service activities in the form of socialization about the operation and maintenance of Communal PLTS. Activities are carried out in the form of presentations/presentations and discussions and questions and answers. After the presentation, a field visit was carried out to the communal/off-grid PLTS installation with a capacity of 10 kWp. The result of this activity is that the people of Tunjungan Village can understand well about the working principles, how to operate and maintain a PLTS installation. This activity, in addition to being attended by village officials and PLTS operators, was also attended by several residents of Tunjungan Village